Synthesis of substituted styrenes and stilbenes mediated by palladium on zirconia - Borate, Hanumant B.; Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Journal of Chemical Research-S, 2008)
Palladium on zirconia has been found to be an effective catalyst for the synthesis of various substituted styrenes and stilbenes, including biologically active natural products, by reaction of aryl halides with olefins.
Keywords: heterogeneous catalyst; palladium on zirconia; stilbenes; styrenes